Silicide Precipitation in Alloy Ti-6AI-5Zr-0.5Mo-0.25Si - Ramachandra C.; Singh V. (My University, 2025)
Silicide precipitation in the titanium alloy containing by wt pct 6Al-5Zr-0.5Mo-0.25Si (Alloy 685) has been investigated using electron diffraction. The solutionizing temperature for this alloy is 1323 K. It is observed that no resolvable silicide precipitates are present in the alloy as received, furnace cooled from 1323 K and aged at 823 K, or oil quenched from 1323 K and aged at 823 K. Specimen solutionized at 1323 K for 30 minutes followed by water quenching and aging at 923 K for 24 hours shows fine precipitates at boundaries of α′ platelets. Diffraction analysis shows that the fine precipitates belong to two different types of identifiable hexagonal silicides similar to those observed by Flower et al in the ternary Ti-5Zr-0.5Si alloy to be (TiZr)5Si3 and another of unknown stoichiometry. However, aging of the water quenched specimens for 24 hours at higher temperatures, 973 K and 1073 K, results in the precipitation of a silicide similar to the latter one. It is analyzed that this silicide has lattice parameters a = 0.702 nm and c = 0.368 nm. Since aging at 973 K and 1073 K gives rise to precipitation of the same silicide, it is concluded that this is the stable silicide in Alloy 685 in the temperature range investigated. © 1982 American Society for Metals and the Metallurgical Society of AIME.